Penerapan Media Flash Card untuk Meningkatkan Kemampuan Membaca Anak di Kelas 1 Madrasah Ibtidaiyah (MI) Humaira - Dina Maryati; Agus Suryana; Siti Hadiyanti Dini I; Herlina (Mimbar Kampus: Jurnal Pendidikan dan Agama Islam, 2025)
This study is intended to determine the steps for using flashcard media in learning Indonesian Language Subjects for grade 1 students at MI Humaira, Bojong Gede District, Bogor Regency. Bogor which is taught using flashcard media. To find out whether flashcard media can foster student learning activity in Indonesian language learning for grade 1 MI Humaira students, Bojong Gede District, Bogor Regency. This research uses 2 cycles of classroom action research methods. It can be seen that students' reading ability has increased each cycle, namely in the pre-cycle there were 9 students or 32%, there was an increase in the first cycle, namely 18 students or 64% and at the end of the second cycle there were 26 students or 93% who completed. Flash card media can foster student learning activity in Indonesian language learning for grade 1 students at MI Humaira, Bojong Gede District, Bogor Regency.